Size-Dependent Graphene Support for Decorating Gold Nanoparticles as a Catalyst for Hydrogen Evolution Reaction with Machine Learning-Assisted Prediction - Boontarika Saeloo; Kulpavee Jitapunkul; Pawin Iamprasertkun; Gasidit Panomsuwan; Weekit Sirisaksoontorn; Tawan Sooknoi; Wisit Hirunpinyopas (ACS Applied Materials & Interfaces, 2023)
GP/AuNPs electrode surface also play crucial roles in enhancing electrolytes for penetration in the electrode, suggesting a highly electrochemical surface area. Moreover, machine learning (Random Forest) was also used to reveal the essential features of the advanced catalytic material design for catalyst-based applications.
Keywords: Electrocatalysts for Energy Conversion; Graphene research and applications; Advancements in Battery Materials